Analysis of society from the point of view of an acting subject - Górniak, Jarosław (Journal of Public Governance, 2013)
The paper presents the theoretical approach to the research of social life based on transcendental realism and methodological individualism (accepting the existence of structured social entities), recognizing the high complexity of social life and its evolutionary character. This position is formulated in opposition to constructivism and holism. The mode of constructing social theories is inspired by a reinterpretation of Alfred Schütz’s approach that focuses on the features of Schütz’s concept which bring him closer to the rational choice theory than to interpretative postmodernism, even though he is often considered as the proponent of the latter. The ideas presented in the paper are close to those developed in the scope of analytical sociology, especially to its emphasis on causal research of social mechanisms and micro-macro relationships.